The Concept of Multiple Intelligence Education From the Quran's Perspective - Muzayyanah Sa'diyah (Journal of Islamic Education Research, 2024)
This research aims to understand the Koran's view of Multiple Intelligences. This research is a literature study that collects data from books, magazines, articles, and works related to the formation of multiple intelligences from the perspective of the Al-Quran. In the Koran, human intelligence is related to faith and religious values. Every child own differences in intelligence. The Qur'an's view of various types of intelligence in Gardner's theory of multiple intelligence is not caused by the evolution of intelligence as proposed by Gardner but has existed since the birth of humans and their natural development. Apart from strengthening this argument, it also criticizes the spiritual references of Gardner's theory of multiple intelligences. This research concludes that each person has a different level of intelligence and continues to develop. According to Gardner, there are nine basic bits of intelligence: verbal intelligence, logical-mathematical intelligence, visual-spatial intelligence, kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, and natural and spiritual intelligence. The Al-Quran reveals language intelligence in surah al-Baqarah verses 31-33 and logical-mathematical intelligence in surah al-Ankabut verse 43. Human visual-spatial intelligence brought by Allah SWT is exposed in surah Hud 37-38 and the Qur'an. A shows human kinesthetic intelligence in surah al-Maidah 31. Allah gave humans rhythmic-musical intelligence to recite the holy verses of the Koran in a beautiful and linguistic style. In surah al-Hujarat verse 13 there is talk about interpersonal intelligence which shows the differences between humans. Allah intrapersonal signals in surah Zariyat 21 and naturalist intelligence in surah Ali Imran 190-191. God's intelligence is demonstrated existentially in surah Zariyat 56.